Case report: Bilateral sudden deafness in acute middle cerebellar peduncle infarction: central or peripheral? - Yuan, Ziyun; Xiang, Lei; Liu, Ran; Yue, Wei (Frontiers in Medicine, 2023)
Background The middle cerebellar peduncle (MCP) is the most common site associated with hearing impairment in acute ischaemic stroke. Narrowing or occlusion of the vertebrobasilar artery due to atherosclerosis is thought to be the main pathogenesis of MCP infarction. Most previous reports of MCP infarction have not been clear whether the patient's hearing impairment is localized to the center or periphery. Case presentation We report 44-year-old man with vertigo, tinnitus, and bilateral sudden sensorineural hearing loss (SSNHL) as the first symptoms. Pure Tone Audiogram revealed complete hearing loss in both ears. Acute bilateral MCP infarction was diagnosed by repeated brain magnetic resonance imaging (MRI). The brainstem auditory evoked potential (BAEP) and the electrocochleography were normal. The otoacoustic emissions showed binaural cochlear dysfunctions. After the antiplatelet, lipid-lowering, steroids and hyperbaric oxygen therapy, the pure-tone average (PTA) showed a clear improvement with 67 decibels (dB) on the right and 73 dB on the left at the 3-month follow-up. Conclusion Vertebrobasilar diseases due to atherosclerosis should be routinely considered in middle-aged and elderly patients with vascular risk factors and bilateral hearing loss. Bilateral SSNHL can be a prodrome of acute MCP infarction and it can be peripheral. Brain MRI, brain magnetic resonance angiogram (MRA), brain and neck computed tomography angiography (CTA), BAEP, otoacoustic emissions, and Pure Tone Audiogram help to localize and qualify the diagnosis. Bilateral SSNHL localized to the periphery usually improves better and has a good prognosis. Early detection of hearing loss and intervention can help patients recover.